Inventory Analysis Using The ABC, VEN and EOQ Methods For Procurement Budget Efficiency Medicine at Tritya Eye Clinic Surabaya - Bima Ardiyanto Wibowo; Ulfi Pristiana; Esti Hari Prastiwi (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
Efficient drug inventory management is a critical factor in ensuring medicine availability and optimizing procurement budgets in healthcare facilities. This study aims to analyze drug inventory at Tritya Eye Clinic Surabaya using the ABC (Always, Better, Control), VEN (Vital, Essential, Non-Essential), and EOQ (Economic Order Quantity) methods to improve procurement budget efficiency. A quantitative descriptive approach with a case study method was employed. Data were collected from drug usage records, stock opname reports, and procurement documents from in 2024. The findings reveal that the combined ABC-VEN method effectively identifies priority drug groups based on consumption value and clinical importance, while the EOQ method determines optimal ordering quantities to minimize total inventory costs. The integrated application of these methods successfully reduces overstock and stockout incidents and enhances procurement budget efficiency. This study recommends inventory management based on historical usage data and strategic classification to achieve more accurate and cost-effective drug procurement planning.